Enforcement of environmental law through citizen lawsuit in administrative court - Putrijanti Aju; Indreswari Tri Laksmi; Yuli Sulistyawan Aditya; Wahyu Ananingsih Sri; Doramia Lumbanraja Anggita (E3S Web of Conferences)
Environmental law had been enforced through by non-litigation or litigation. CLS is a litigation strategy used to file lawsuit against government for failing to deliver and fulfill citizen’s rights. The damage of the environmental can be harmful to humans. CLS used to file to General Court, however some cases were granted, and others were denied. The CLS regulation for environmental dispute existed following the Supreme Court Regulation Number 1 of 2023 which provided Guidance to Adjudicate Environmental Cases. Based on research as spesific finding there was no CLS was presented to the Administrative Court one year following the stipulation. Despite the importance of technical assistance for judges, the Supreme Court only provided it in 2024.The Administrative Court weilds significant power and authority to enforce environmental laws and protect the environmental for future generations. Specifically, CLS it demonstrates that government through the court body, tried to fulfill environmental citizen’s rights.